Investigating rodents and environmental samples as possible sources of Leptospira infections in the Mnisi communal area, Bushbuckridge, South Africa - Van Wyk, Illana (University of Pretoria, 2023)
Mini Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2023.